Tissue inhibitors of metalloproteinases: evolution, structure and function. - Brew, K; Dinakarpandian, D; Nagase, H (2000)
The matrix metalloproteinases (MMPs) play a key role in the normal physiology of connective tissue during development, morphogenesis and wound healing, but their unregulated activity has been implicated in numerous disease processes including arthritis, tumor cell metastasis and atherosclerosis. An important mechanism for the regulation of the activity of MMPs is via binding to a family of homologous proteins referred to as the tissue inhibitors of metalloproteinases (TIMP-1 to TIMP-4). The two-domain TIMPs are of relatively small size, yet have been found to exhibit several biochemical and physiological/biological functions, including inhibition of active MMPs, proMMP activation, cell growth promotion, matrix binding, inhibition of angiogenesis and the induction of apoptosis. Mutations in TIMP-3 are the cause of Sorsby's fundus dystrophy in humans, a disease that results in early onset macular degeneration. This review highlights the evolution of TIMPs, the recently elucidated high-resolution structures of TIMPs and their complexes with metalloproteinases, and the results of mutational and other studies of structure-function relationships that have enhanced our understanding of the mechanism and specificity of the inhibition of MMPs by TIMPs. Several intriguing questions, such as the basis of the multiple biological functions of TIMPs, the kinetics of TIMP-MMP interactions and the differences in binding in some TIMP-metalloproteinase pairs are discussed which, though not fully resolved, serve to illustrate the kind of issues that are important for a full understanding of the interactions between families of molecules.